Effects of C/N Ratio for Bi-Culture of Litopenaeus vannamei (Boone, 1931) and Macrobrachium rosenbergii (de Man, 1879) in a Molasses Based Biofloc System - Halim, Md. Abdul; Aziz, Dania; Arshad, Aziz; Wong, Nur Leena W. S.; Karim, Murni Marlina; Syukri Ismail, Muhammad Fadhil; Rahi, Md. Lifat (Wiley, 2025)
This study evaluated the effects of different C/N ratios (C10–N, C15–N, C20–N and C25–N, compared to C0–N as control) on growth, water quality, proximate composition, bacterial loads and total haemocyte counts (THCs) of shrimp (Litopenaeus vannamei) and prawn (Macrobrachium rosenbergii) post larvae in a biofloc-based nursery bi-culture system, aiming to optimize C/N ratios for sustainability and production efficiency over 6 weeks. Molasses was used as a carbon source, and water salinity was maintained at 15 ppt. In total, 15 cylindrical plastic tanks (125 L water-holding capacity, 59 cm × 56 cm) were used and filled up each 100 L water for rearing 1500 PL of the two species (750 L. vannamei and 750 M. rosenbergii). At the end of the experiment, significantly higher (p < 0.05) specific growth rate (SGR, % per day) (9.77) and survivability (95.33%) for L. vannamei were recorded in C10–N compared to the other treatments. For M. rosenbergii, the significantly higher (p < 0.05) SGR (% per day) (5.77) was recorded in C25–N, whereas the higher survival rate was found at C10–N (90.67%). The best feed conversion ratio was obtained at C10–N for L. vannamei (1.58), whereas for M. rosenbergii, it was obtained at C25–N (2.43). Significantly the higher (p < 0.05) THCs (L. vannamei = 40.63 × 105 and M. rosenbergii = 31.25 × 105) of both species were obtained at C10–N. The experimental C–N ratios led to a significant increase (p < 0.05) in total microbial loads (116.6–355 × 109 CFU mL−1) compared to the control (18.40 × 106 CFU mL−1). Moreover, all tested water quality parameters remained within the optimal range across the treatments. The study concluded that a C:N ratio of 10:1 provides the highest economic return, making it the optimal ratio for biofloc-based nursery bi-culture of L. vannamei and M. rosenbergii.